Gender Differentiation and Perceived Ease of Usage of Electronic Resources by University Students in Selected Private Universities in Nigeria - Ebijuwa, Adefunke S. (Journal of Information and Knowledge, 2018)
The importance of electronic resources as the bedrock of provision of accurate, easy to access, relevant and, up-to-date information in learning and research cannot be over-emphasized. Through electronic resources’ use students have access to global resources for their academic activities. However, despite the potential benefit electronic resources holds for effective learning and research by students, studies have shown that their proper and maximum use is still a matter for discussion. This study, therefore, examined perceived ease of use and gender differences as factors influencing electronic resources use by students in selected private universities in Nigeria. The study adopted a descriptive survey design with a population of 4,452 undergraduate students. Multi-stage sampling technique was used in selecting the sample size for the study. Questionnaire was used for data collection which was analysed using descriptive statistics, standard deviation, Cross Tab Analysis (Pearson Chi-Square) and T-test. The result of the analysis revealed low usage of electronic resources by the students. It further revealed a renowned difference in gender differentiation. Also, a significant proportion of the students did not use electronic resources frequently. In addition, this study found that the respondents perceived use of electronic resources easy to use. However, the major constraints to electronic resources use by students were lack of knowledge of search techniques to retrieve information effectively, insufficient user training, lack of awareness, download delay and constant power failure. The findings indicated that both perceived ease of use and gender significantly influenced students’ use of electronic resources. Based on the findings, the study recommends that concerted effort by university libraries may ameliorate the problems of low use. Therefore, libraries should: integrate e-resources search techniques and retrieval skills into the curriculum of Use of Library taught at the universities, create awareness strategies by under taking university-wide lecture on access, promote e-resources through the use of e-mail alert and social media platforms, adopt various motivational strategies to encourage the use of electronic resources and should also endeavour to have standby generator, Inverter or Solar Power to limit the problem of constant power failure.